2015
DOI: 10.2105/ajph.2014.301935
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dementia and Alzheimer’s Disease in an Older Population: Updated Incidence and Life Expectancy With and Without Dementia

Abstract: Efforts to delay onset of dementia, if successful, would likely benefit older adults of all ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
130
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 26 publications
10
130
0
2
Order By: Relevance
“…For example, according to CHAP estimates, approximately 910,000 people age 65 or older developed Alzheimer's dementia in the United States in 2011, a number that would be expected to be even higher in 2020 if CHAP estimates were available for that year 209 . A study using data from the Adult Changes in Thought study, a cohort of members of Kaiser Permanente (formerly Group Health), a health care delivery system in the Northwest United States, reported similar incidence rates to the CHAP study 210 . The number of new cases of Alzheimer's increases dramatically with age: according to estimates from CHAP, in 2011 the average annual incidence in people age 65‐74 was 0.4% (meaning four of every 1,000 people age 65‐74 developed Alzheimer's dementia in 2011); in people age 75‐84, the annual incidence was 3.2% (32 of every 1,000 people); and for age 85 and older (the “oldest‐old”), the incidence was 7.6% (76 of every 1,000 people) 209 .…”
Section: Prevalencementioning
confidence: 91%
See 2 more Smart Citations
“…For example, according to CHAP estimates, approximately 910,000 people age 65 or older developed Alzheimer's dementia in the United States in 2011, a number that would be expected to be even higher in 2020 if CHAP estimates were available for that year 209 . A study using data from the Adult Changes in Thought study, a cohort of members of Kaiser Permanente (formerly Group Health), a health care delivery system in the Northwest United States, reported similar incidence rates to the CHAP study 210 . The number of new cases of Alzheimer's increases dramatically with age: according to estimates from CHAP, in 2011 the average annual incidence in people age 65‐74 was 0.4% (meaning four of every 1,000 people age 65‐74 developed Alzheimer's dementia in 2011); in people age 75‐84, the annual incidence was 3.2% (32 of every 1,000 people); and for age 85 and older (the “oldest‐old”), the incidence was 7.6% (76 of every 1,000 people) 209 .…”
Section: Prevalencementioning
confidence: 91%
“…But when it comes to differences in the actual risk of developing Alzheimer's or other dementias for men and women of the same age, findings have been mixed. Most studies of incidence in the United States have found no significant difference between men and women in the proportion who develop Alzheimer's or other dementias at any given age 71,210,213‐215 . However, some European studies have reported a higher incidence among women at older ages, 216,217 and one study from the United Kingdom reported higher incidence for men 218 .…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…); (ii) women with Alzheimer's disease outlive men with Alzheimer's disease (Tom et al . ); and (iii) the prevalence of Alzheimer's disease is higher in women than it is in men (Tom et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…); and (iii) the prevalence of Alzheimer's disease is higher in women than it is in men (Tom et al . ). All this implies that women with Alzheimer's disease are more likely to experience bereavement.…”
Section: Introductionmentioning
confidence: 99%